Fractionation - Al- Haj Ibrahim, Hassan (IntechOpen, 2019)
Fractionation, in the most general sense, could mean any process whereby a mixture is separated into different components or fractions. Examples of fractionation processes include dephlegmation, fractional distillation, fractional freezing, fractional melting, isotope fractionation, and other separation techniques. Of the many and varied separation processes available, fractionation plays a major part, and capital investment in fractionation equipment and processes may form a significant fraction of industrial processing investment. Fractionation as a separation technique is extensively used in widely diverse areas such as the application of geochemical fractionation of metals in sediments of water reservoirs, fractionation of polysaccharides from selected mushroom species, and fractional distillation of bio-oil produced by pyrolysis of certain palm seeds.